A note on identifying a transmission factor in room acoustics - Ohta, M.; Ogawa, H. (Archives of Acoustics, 2005)
In this study, as a concrete example of the non-linear inverse problem in indoor sound fields, a complex sound fluctuation leaked through an aperture gap in the partition door of a coupled room under the actual sound environment has been discussed. A probability evaluation theory introducing a simple stochastic inverse system model has been proposed first especially from an object-oriented viewpoint. More concretely, in order to evaluate the output response probability distribution of the acoustic intensity in the sound receiving room, after introducing time-averaged stochastic variables, we have identified functionally the leakage property as some variability of a transmission factor. Then, we have predicted the output response probability distribution for a new arbitrary stochastic input once after establishing a prediction theory for the probability distribution of a multiplicative model. Finally, an effectiveness of the proposed theory has been experimentally confirmed too by an application to actual indoor sound field data.